Patch clamp-assisted single neuron lipidomics - Collin B. Merrill (Scientific Reports, 2017)
Abstract Our understanding of the physiological and pathological functions of brain lipids is limited by the inability to analyze these molecules at cellular resolution. Here, we present a method that enables the detection of lipids in identified single neurons from live mammalian brains. Neuronal cell bodies are captured from perfused mouse brain slices by patch clamping, and lipids are analyzed using an optimized nanoflow liquid chromatography/mass spectrometry protocol. In a first application of the method, we identified more than 40 lipid species from dentate gyrus granule cells and CA1 pyramidal neurons of the hippocampus. This survey revealed substantial lipid profile differences between neurons and whole brain tissue, as well as between resting and physiologically stimulated neurons. The results suggest that patch clamp-assisted single neuron lipidomics could be broadly applied to investigate neuronal lipid homeostasis in healthy and diseased brains.